Backstepping design of robust state feedback regulators for second order hyperbolic PIDEs - Deutscher, Joachim; Kerschbaum, Simon (IFAC-PapersOnLine, 2016)
This contribution considers the backstepping design of robust state feedback regulators for second order hyperbolic partial integro-differential equations (PIDEs). To this end, the internal model principle is applied, which amounts to designing a stabilizing backstepping controller for a PIDE-ODE system. By transforming this system into a PDE-ODE cascade a systematic design procedure is presented. Then, robust output regulation is verified for non-destabilizing model uncertainties by means of the extended regulator equations. The results of the article are applied for the robust output regulation of a shear beam with a destabilizing boundary conditio
Keywords: backstepping; Distributed-parameter systems; hyperbolic systems; robust output regulation; state feedback